Special representative actions, the insurance value of audits, and investor protection: An empirical study based on the ruling against Kangmei Pharmaceutical Co. Ltd - Daoguang Yang; Hongling Han; Yidan Mao; Siyi Liu (China Journal of Accounting Studies (CJAS), 2023)
The ruling against the Kangmei Pharmaceutical Co., Ltd's financial fraud was the first special representative action under China's new Securities Law, serving as a milestone in investor protection in China. Exploiting the natural experiment provided by the ruling, we empirically test the insurance value of audits and find a negative market reaction of the client firms audited by the accounting firms that were still being sued as of the date of Kangmei ruling (i.e., the sued accounting firms). Further, this reaction is weakened when the solvency of the sued accounting firms or the client firms is high, and is intensified when the client firms have high litigation risk. The ruling also eroded investors' trust in the financial statements for the year 2020 that were audited by the sued accounting firms. Overall, we provide important evidence on the effect of special representative actions from the perspective of audit insurance hypothesis.
Keywords: 650; Special representative actions; investor protection; insurance hypothesis; new Securities Law